Organizational role stress indices affecting burnout among nurses at Shah Alam Specialist (SALAM) Hospital / Norazimah Jamaludin - Jamaludin, Norazimah (Faculty of Business and Management, 2009)
Organizational role stress and burnout are major factors that nurses have to deal with often while in their work environment. This research was aimed to identify stressors, and the impact that burnout has on patient care and the nurses themselves. The purpose of this research is to examine the relationship on burnout among nurse with the five prerequisites; inter-role distance, role stagnation, role expectation conflict, role erosion, and role overload in Shah Alam Specialist Hospital. This study was conducted using a convenience sample of 50 nurses at the hospital. Maslach Burnout Inventory (MBI; Maslach & Jackson, 1981), and Organizational Role Stress Scale (Udai Pareek, 1993) was used to measure levels of burnout and role stress. All data was distributed and collected by the researchers. Ethical considerations have been taken into account to uphold confidentiality and prevent biases in the study. Once the respondent returns back the questionnaire, all data and information gathered were coded, process and analyze byusing Statistical package for Social Science (SPSS) version 16.0 to produce a relevant and accurate result. According to the nurses' views, the findings are as follows: (1) there is a relationship between inter-role distance and burnout, (2) there is a relationship between role stagnation and burnout (3) there is a relationship between role expectation conflict and burnout,(4) there is a relationship between role erosion and burnout, (5) there is a relationship between role overload and burnout. The findings give a better understanding about level of employee burnout in a company.